Chickenpox - Gordon, Sharon; Vargus, Nanci Reginelli; Waddell, Jayne L. (New York, 2002)
Provides a brief introduction to the effects of the chicken pox virus, its possible prevention, and ways to make the patient more comfortable.
Includes index.
Keywords: Chickenpox; Juvenile literature; Chicken pox; Diseases